Wolf spider (Araneae, Lycosidae) fauna of an old abandoned agricultural village of Mutenia in Finnish Lapland - Itämies, Juhani; Nenonen, Olli (Memoranda Societatis pro Fauna et Flora Fennica, 2009)
The study was carried out in the Mutenia meadow area on the northern shore of Lokka reservoir in Finnish Lapland in the years 2000–2002.Mutenia is an old Lappish agricultural village, from which the last inhabitants moved away in the late 1960s. It has been kept as meadow bymowing. The material was collected with pitfall traps and window trapsmade of balcony flower pots situated on the ground. The total number of species was 17, including 1816 individuals. Pardosa palustris (Linnaeus) (35.6%) and P. sphagnicola (Dahl) (33.0%) were the twomost abundant species. The next two in frequency were Alopecosa aculeata (Clerck) (14.4%) and A. pulverulenta (Clerck) (6.2%). Pardosa lasciva L. Koch and P. atrata (Thorell) represented the northern fauna element, while P. fulvipes (Collet) and P. paludicola (Clerck) belonged to a southern type. There were two new biogeographical records: Pardosa fulvipes and P. pullata (Clerck).